The construction of the evaluation system of nurses' post‐training and the application of the system in 25 grade‐A general hospitals in China. Issue 1 (14th October 2020) - Jiao, Linlin; Sui, Yuanda; Yang, Guihua; Wang, Pulin; Li, Qiaofeng; Chen, Junhong; Liu, Lili; Yang, Chunling
Abstract: Aims: To make the evaluation more scientific, structured and systematic, this study aims to develop an evaluation index system for nurses training and to explore clinical effect of system. Design: The evaluation index system of nurses' post‐training was constructed using the Delphi method. Methods: Introducing the system, we used the pre‐work training of new nurses as an example for discussing the specific implementation scheme of the system. Twenty‐five tertiary and first‐class general hospitals in 14 provinces and municipalities were evaluated on the spot, and the application effect of the system was evaluated comprehensively. Results: The index system consisted of three first‐grade indexes, seven second‐grade indexes and 23 third‐grade indexes. There were three levels in teaching and training ability, and the distance had statistical significance.